Non-stationary Watermark-Based Attack Detection to Protect Cyber-Physical Control Systems - Jose Rubio-Hernan; Luca De Cicco; Joaquin Garcia-Alfaro (Emerging Trends in Cybersecurity Applications, 2023)
This chapter addresses security issues in cyber-physical industrial systems. Attacks against these systems shall be handled both in terms of safety and security. Networked control technologies imposed by industrial standards already cover the safety dimension. From a security standpoint, the literature has shown that using only cyber information to handle the security of cyber-physical systems is not sufficient, since physical malicious actions, that can threaten the correct performance of the systems, are ignored. For this reason, cyber-physical systems should be protected from threats to their cyber and physical layers. Some authors handle the attacks by using physical attestations of the underlying processes. For instance, the use of physical watermarking can complement the protection techniques at the cyber layer, in order to ensure the truthfulness of the process. These detectors work properly if the adversaries do not have enough knowledge to mislead cross-layer (e.g., cyber and physical) data. Nevertheless, adversaries able to acquire enough knowledge from both layers may evade detection.